Sedimentary Signatures of Persistent Subglacial Meltwater Drainage From Thwaites Glacier, Antarctica - Lepp, A. P.; Simkins, L. M.; Anderson, J. B.; Clark, R. W.; Wellner, J. S.; Hillenbrand, C-D.; Smith, J. A.; Lehrmann, A. A.; Totten, R.; Larter, R. D.; Hogan, K. A.; Nitsche, F. O.; et al. (Frontiers in Earth Science, 2022)
Subglacial meltwater drainage can enhance localized melting along grounding zones and beneath the ice shelves of marine-terminating glaciers. Efforts to constrain the evolution of subglacial hydrology and the resulting influence on ice stability in space and on decadal to millennial timescales are lacking. Here, we apply sedimentological, geochemical, and statistical methods to analyze sediment cores recovered offshore Thwaites Glacier, West Antarctica to reconstruct meltwater drainage activity through the pre-satellite era. We find evidence for a long-lived subglacial hydrologic system beneath Thwaites Glacier and indications that meltwater plumes are the primary mechanism of sedimentation seaward of the glacier today. Detailed core stratigraphy revealed through computed tomography scanning captures variability in drainage styles and suggests greater magnitudes of sediment-laden meltwater have been delivered to the ocean in recent centuries compared to the past several thousand years. Fundamental similarities between meltwater plume deposits offshore Thwaites Glacier and those described in association with other Antarctic glacial systems imply widespread and similar subglacial hydrologic processes that occur independently of subglacial geology. In the context of Holocene changes to the Thwaites Glacier margin, it is likely that subglacial drainage enhanced submarine melt along the grounding zone and amplified ice-shelf melt driven by oceanic processes, consistent with observations of other West Antarctic glaciers today. This study highlights the necessity of accounting for the influence of subglacial hydrology on grounding-zone and ice-shelf melt in projections of future behavior of the Thwaites Glacier ice margin and marine-based glaciers around the Antarctic continent.